Non-additive strong gene interactions cause striking differences in organ pathology and cytokine response in Leishmaniasis - Sohrabi, Yahya; Kobets, Tatyana; Volkova, Valeriya; Javorková, Eliška; Krayem, Imtissal; Zajícová, Alena; Havelková, Helena; Svobodová, Milena; Holáň, Vladimír; Demant, Peter; Lipoldová, Marie (Frontiers in Immunology, 2025)
The mouse strain O20 is highly resistant to parasite Leishmania major. O20 mice differed from all resistant strains tested until now, as they harbored parasites in their organs, but upon exposure to soluble Leishmania antigen (SLA) their splenocytes did not respond by cytokine production and their macrophages did not produce NO, suggesting a novel mechanism of resistance. Another resistant strain C57BL/10 (B10) harbors similar numbers of parasites as O20 in its organs and its splenocytes respond to SLA by production of IFNγ, but not IL-4. They also produce IL-2, IL-6, IL-10 and IL-17. Macrophages respond to SLA by NO production. Strain B10.O20 was derived from a cross of these two resistant strains. B10 provided 96.4% of its genome and O20 contributed 3.6% of its genome. Unexpectedly, this very limited difference between the two strains resulted in the very large phenotypic effects. B10.O20 was susceptible to L. major, as it exhibited large skin lesions, high parasite numbers in skin and lymph nodes, and a massive spleen infiltration by CD11b+CD193+ and CD11b+Gr1+ cells. Thus, a small percentage of genes of the resistant strain O20 in the genome of the second resistant strain B10 resulted in high susceptibility to L. major. After stimulation with SLA, splenocytes of B10.O20 produced significantly higher levels of all Th1, Th2 and Th17 cytokines than both its parental strains B10 and O20. This suggested a chronic inflammation with imbalance of several arms of immune response. In summary, the responses of strains B10.O20 and O20 to L. major revealed novel disease phenotypes that have not been observed previously in mice but they were seen in several clinical studies of human leishmaniasis. The studies of heterogeneity of defensive strategies of mouse strains may guide development of effective antileishmanial therapies or vaccine development and it could serve as a basis for investigation of asymptomatic responses to other infectious diseases.